2019
DOI: 10.15666/aeer/1703_59355951
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, Ecology and Phylogeny of Banana Streak Badnavirus (Bsv) and Cucumber Mosaic Cucumovirus (Cmv) in Musa Sp. Production Areas of the Mediterranean Coastline of Turkey

Abstract: Occurrence, ecology and phylogeny of banana streak badnavirus (BSV) and cucumber mosaic cucumovirus (CMV) in Musa sp. production areas of the Mediterranean coastline of Turkey -5935 -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Mixed viral infections are frequent in perennial and vegetative plants. Likewise, the high prevalence of mixed infection of CMV with BBTV or BSV, which was also examined by serological tests and PCR-based methods ( Fidan & Koc, 2019 ; Liu et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mixed viral infections are frequent in perennial and vegetative plants. Likewise, the high prevalence of mixed infection of CMV with BBTV or BSV, which was also examined by serological tests and PCR-based methods ( Fidan & Koc, 2019 ; Liu et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…In banana plants, BBTV and CMV are mainly transmitted by vector insects, such as aphids. CMV infection is found in diverse hosts, not only in cultivated vegetables such as melon, pepper, tomato, and squash, but also in bananas through aphid transmission ( Fidan & Koc, 2019 ). Further, BSV infection in bananas could occur through transmission by mealybugs in the field.…”
Section: Discussionmentioning
confidence: 99%
“…A new degenerate, inosine-containing diagnostic primer was designed to improve the inclusiveness of the detection protocol, which failed to detect these novel isolates. In fact, this kind of primer could help to overcome the high genetic diversity of the virus, even if a lower sensitivity could sometimes result from the degeneracy and inosine contents of the primers [ 9 , 13 , 14 ]. The new primer detected BanMMV infection in two samples that tested negative with the existing primer, but failed to detect three infections among the 110 tested accessions.…”
Section: Discussionmentioning
confidence: 99%
“…‘Pisang Awak’, ABB genome). BanMMV often occurs as a mixed infection with other banana-infecting viruses such as banana streak viruses (BSV) and cucumber mosaic virus (CMV), and the mosaic symptoms of BanMMV may be masked by those of the other viruses [ 1 , 13 , 14 ]. On the other hand, previous studies reported that, in Guadeloupe, infection by BanMMV exacerbated the symptoms of CMV causing leaf necrosis symptoms compared with mosaic symptoms from CMV infection alone [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The period of latency of the virus to showcase symptoms in the infected plants is not only a threat to the domestic market especially where it is vegetatively propagated but also to international germplasm exchange [20]. The tissue culture planting materials that look prima facie healthy, especially have to be indexed for the presence of this virus [21].…”
Section: Introductionmentioning
confidence: 99%